One Religion, Two Tales: Religion and Happiness in Urban and Rural Areas of China - Jing Hua Zhang; Wen Chi Zou; Xiao Yang Jiang (Religions, 2019)
Most previous studies performed in Western social contexts have revealed that religion can influence an individual’s sense of happiness. Few studies have sought to clarify the influence of religion in a Chinese social context, however, and there has been no study specifically about the potential differences in the dichotomous social environments of urban and rural areas in China. Via the nationwide survey data of the 2007 Spiritual Life Study of Chinese Residents (SLSC), this study examines the association between religion and happiness among urban and rural residents of China. The results reveal that there is a generally positive association between religion and happiness among those with religious affiliations in China. Regardless of affiliation with Buddhism or Protestantism, there is a strong positive association among rural respondents, an insignificant association among urban respondents, and mixed results among town residents.